Propagation of Mitochondria-Derived Reactive Oxygen Species within the Dipodascus magnusii Cells - Anton G. Rogov; Tatiana N. Goleva; Khoren K. Epremyan; Igor I. Kireev; Renata A. Zvyagilskaya (MDPI AG, 2021)
Mitochondria are considered to be the main source of reactive oxygen species (ROS) in the cell. It was shown that in cardiac myocytes exposed to excessive oxidative stress, ROS-induced ROS release is triggered. However, cardiac myocytes have a network of densely packed organelles that do not move, which is not typical for the majority of eukaryotic cells. The purpose of this study was to trace the spatiotemporal development (propagation) of prooxidant-induced oxidative stress and its interplay with mitochondrial dynamics. We used Dipodascus magnusii yeast cells as a model, as they have advantages over other models, including a uniquely large size, mitochondria that are easy to visualize and freely moving, an ability to vigorously grow on well-defined low-cost substrates, and high responsibility. It was shown that prooxidant-induced oxidative stress was initiated in mitochondria, far preceding the appearance of generalized oxidative stress in the whole cell. For yeasts, these findings were obtained for the first time. Preincubation of yeast cells with SkQ1, a mitochondria-addressed antioxidant, substantially diminished production of mitochondrial ROS, while only slightly alleviating the generalized oxidative stress. This was expected, but had not yet been shown. Importantly, mitochondrial fragmentation was found to be primarily induced by mitochondrial ROS preceding the generalized oxidative stress development.